2016
DOI: 10.1155/2016/4340916
|View full text |Cite
|
Sign up to set email alerts
|

An Enhanced Collaborative Optimization Approach with Design Structure Matrix Algorithms to Group and Decouple Multidisciplines

Abstract: To improve the solution efficiency and reliability of multidisciplinary design optimization (MDO), an enhanced MDO approach, called sequenced collaborative optimization (SCO), is proposed. The proposed approach introduces the design structure matrix (DSM) to describe the coupling effects among disciplines and aggregates those mutually coupling disciplines into the strong tie groups among similar ones and the weak tie among heterogeneous ones through clustering algorithms. Further, those in the same group are s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 16 publications
0
1
0
Order By: Relevance
“…This review showed that existing MDO architectures are not employed for electric motor design. In other engineering disciplines, different works that tackle the systematic derivation of MDO architectures which could be adapted for the framework exist, e.g., [113,123,126].…”
Section: Architecture Adaptationmentioning
confidence: 99%
“…This review showed that existing MDO architectures are not employed for electric motor design. In other engineering disciplines, different works that tackle the systematic derivation of MDO architectures which could be adapted for the framework exist, e.g., [113,123,126].…”
Section: Architecture Adaptationmentioning
confidence: 99%
“…A Boolean value, that is, "1" or "0," can represent whether one discipline depends on another [35,36]. The Boolean DSM could also be employed to model and solve Boolean Dynamical Systems [37,38].…”
Section: Discipline Dependence Representation Of Coupled Systemsmentioning
confidence: 99%